1962
DOI: 10.1530/jrf.0.0030041
|View full text |Cite
|
Sign up to set email alerts
|

Sex Behaviour of Purebred and Crossbred Merino and Blackhead Persian Ewes

Abstract: Data are presented on a number of aspects of the sex behaviour of four breeds of sheep in South Africa. In crossbred Dorset Horn : Persian ewes, puberty was reached at an average age of 399-7 days. Autumn-born lambs, however, showed their first signs of oestrus 67-2 days later than those born in winter. Ewes generally exhibited a seasonal pattern in their sex activity with a peak in autumn and the lowest level in spring. This was most pronounced in the Merino and least so in Blackhead Persians. Crossbred ewes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1967
1967
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Its average length of 36 h (range 24 to 48 h) was similar to that found for the Dorset Horn, Suffolk and fat-tailed ewes (Hafez, 1952;Joubert, 1962;Sefidbakht, Mostafavi and Farid, 1978). Its average length of 36 h (range 24 to 48 h) was similar to that found for the Dorset Horn, Suffolk and fat-tailed ewes (Hafez, 1952;Joubert, 1962;Sefidbakht, Mostafavi and Farid, 1978).…”
supporting
confidence: 79%
“…Its average length of 36 h (range 24 to 48 h) was similar to that found for the Dorset Horn, Suffolk and fat-tailed ewes (Hafez, 1952;Joubert, 1962;Sefidbakht, Mostafavi and Farid, 1978). Its average length of 36 h (range 24 to 48 h) was similar to that found for the Dorset Horn, Suffolk and fat-tailed ewes (Hafez, 1952;Joubert, 1962;Sefidbakht, Mostafavi and Farid, 1978).…”
supporting
confidence: 79%
“…The duration of oestrus in the sheep has been found to differ from one breed to another (Hafez, 1952;Joubert, 1962), but Asdell (1964) concluded that "the mean heat period (of the sheep) is from 30 to 36 hours, with little differences between breeds". The Finnish Landrace, however, has been found by Donald & Read (1967) to have an oestrous period of 48 to 72 hr, much longer than that of British breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable variation is to be found in the published estimates of the length of heat in sheep (Quinlan & Mare, 1931; Grant, 1934;McKenzie & Terrill, 1937;Hulet, Blackwell, Ercanbrack, Price & Wilson, 1962;Hunter, 1962;Joubert, 1962;Joubert & Louw, 1964;and others). Since overt characteristics accompanying oestrus are almost completely absent in the ewe, these reports have been based on observations of mating behaviour during continuous or, more commonly, intermittent periods of association of the sexes.…”
Section: Introductionmentioning
confidence: 99%